Pemanfaatan Limbah Minyak Jelantah Menjadi Sabun Padat - Anita Anita; Fatmawati Muharram; Dewi Arisanti; Darmaway Rauf; Suardi Suardi; Bambang Ariyanto (Lembaga Penelitian Dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2021)
Used cooking oil contains compounds that are carcinogenic which pose a risk to human health. Waste cooking oil is also at risk for areas where used cooking oil is disposed, for example into sewers or into the ground. This can contaminate soil and water, thereby endangering humans or the surrounding environment. Therefore, serious action is needed on the use of used cooking oil waste so that it can be utilized optimally as a staple in the soap processing process. Through community service activities which are one of the implementations of the Tridharma of Politeknik Kesehatan Muhammadiyah Makassar Study Program of Medical Laboratory Technology, then education is carried out in the form of counseling to the taklim assembly team at the Al-Hidayah Perumnas Antang Makassar Mosque regarding the use of used cooking oil into solid laundry soap. From this community service activity, it can be concluded that the knowledge of the taklim team at the Al-Hidayah Mosque in Manggala Village, Manggala District, Makassar City regarding the dangers of used cooking oil waste for health and how to process used cooking oil into solid soap.